Efficacy and Safety of the Triple Therapy Containing Ilaprazole, Levofloxacin, and Amoxicillin as First-Line Treatment in Helicobacter pylori Infections - Hyo Jun Ahn; Dong Pil Kim; Myeong Su Chu; Hyeon Jeong Yun; Seok-Hwan Kim; Seung Woo Lee; Dong Soo Lee (Gastroenterology Research and Practice)
Background and Aims. To establish the efficacy and safety of ilaprazole, levofloxacin, and amoxicillin as a first-line eradication treatment for Helicobacter pylori. Methods. Patients with gastric ulcer, duodenal ulcer, or gastritis, as detected by esophagogastroduodenoscopy with confirmed H. pylori infection between September 2014 and November 2015, were enrolled in the study. All participants received ilaprazole (10 mg bid), levofloxacin (500 mg bid), and amoxicillin (1000 mg bid) for 10 days. H. pylori eradication was confirmed by a 13C-urea breath test at 6–8 weeks after the end of treatment. Results. Of 84 patients included in the analysis, the eradication rate was 88.8% in the per protocol group (n=80). Demographic factors such as age, gender, body mass index (BMI), alcohol, smoking, hypertension, diabetes mellitus, and peptic ulcer did not affect the eradication rate. However, multivariate analysis showed that overweight patients and patients with cerebrovascular accident (CVA) had a significantly lower eradication rate than patients with normal BMI and without CVA. Laboratory test results did not change significantly after treatment. A total of six (7.5%) patients developed eight adverse reactions. Conclusions. A 10-day triple therapy containing ilaprazole, levofloxacin, and amoxicillin is a safe alternative first-line eradication treatment for H. pylori.